Rekonstruksi Teori Emansipasi Wanita melalui Analisis QS. Al Hujuraat Ayat 13: Membangun Pemahaman Holistik terhadap Hak-Hak Perempuan dalam Perspektif Islam - Munaji, Munaji; Syukkur, Abdul (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2024)
This study aims to reconstruct the theory of women's emancipation through QS analysis. Al-Hujura atAyat 13, with a focus on building a holistic understanding of women's rights from an Islamic perspective. Along with the dynamics of women's emancipation today, this study highlights the links between emancipation theory and its implementation in everyday life. General discourse regarding women's emancipation, especially regarding careers, can limit women's life choices. Therefore, the emphasis on understanding that emancipation should provide choices and equality does not limit the diversity of women's life choices. An in-depth analysis of Islamic interventions in the context of emancipation theory highlights fundamental questions about the explicit goals of emancipation. It is important to understand whether emancipation is simply to support women's career trends or also aims to address issues of racism and equality. This study encourages modern Islamic society to carry out in-depth analysis of new cultural phenomena and update thinking patterns in order to face risks and controversies during the implementation of reform ideas. The history of women's suffering before the rise of the emancipation movement is illustrated, showing how the emancipation of women in Indonesia, pioneered by RA Kartini, has changed the social paradigm. The theory and application of emancipation, as outlined by Frantz Fanon and Mary Wollstonecraft, provides a broad perspective on women's struggle for liberation from legal restrictions and equality. However, it should be remembered that emancipation should not exclude women's rights as housewives. The study also highlights the concept of equality in Islam and how the Koran emphasizes that a person's glory in the sight of Allah depends on the level of piety, not gender. By understanding the anatomical differences between men and women, Islam recognizes the different but equal functional roles of both. Therefore, women's emancipation in the Islamic context should provide freedom of choice without limiting life choices, respecting the role of housewife, and balancing career and family life. Key words: Reconstruction, Emancipation, Women